Ectopic POU5F1 in the male germ lineage disrupts differentiation and spermatogenesis in mice. Issue 4 (October 2016) - Zheng, Yu; Phillips, LeAnna J; Hartman, Rachel; An, Junhui; Dann, Christina T
Abstract : Expression levels of the pluripotency determinant, POU5F1, are tightly regulated to ensure appropriate differentiation during early embryogenesis. POU5F1 is also present in the spermatogonial stem cell/progenitor cell population in mice and it is downregulated as spermatogenesis progresses. To test if POU5F1 downregulation is required for SSCs to differentiate, we produced transgenic mice that ubiquitously express POU5F1 in Cre-expressing lineages. Using a Vasa-Cre driver to produce ectopic POU5F1 in all postnatal germ cells, we found that POU5F1 downregulation was necessary for spermatogonial expansion during the first wave of spermatogenesis and for the production of differentiated spermatogonia capable of undergoing meiosis. In contrast, undifferentiated spermatogonia were maintained throughout adulthood, consistent with a normal presence of POU5F1 in these cells. The results suggest that POU5F1 downregulation in differentiating spermatogonia is a necessary step for the progression of spermatogenesis. Further, the creation of a transgenic mouse model for conditional ectopic expression of POU5F1 may be a useful resource for studies of POU5F1 in other cell lineages, during tumorogenesis and cell fate reprogramming.